STRESSED CONDITION OF THE WRAPPING WITHOUT-DRIVE HYDROTECHNICAL TUNNEL OF THE CIRCULAR FORM, PROPOSED IN ANISOTROPIC ROCK GROUND - D. T. Bautdinov; M. M. Djamaludinov; K. S. Zhukova (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives. The aim of the study is a parametric analysis of the stress-free lining of a pressureless hydraulic tunnel of circular section, and adjacent anisotropic rock from its own weight of the ground medium at different ratios of the elastic characteristics of the ground medium in orthogonal directions using a transversely isotropic medium model.Method. The calculation of a large-length hydraulic tunnel laid in strong transversely isotropic rocky ground is reduced to the problem of plane deformation of the theory of elasticity for a transversely isotropic medium containing tunnel development. A model of a transversely isotropic medium (a special case of an anisotropic medium) was used, in which the ground in one plane possesses the characteristics of an isotropic medium (the isotropy plane), and in the perpendicular direction, characteristics different from the isotropic medium. The finite element method was used using the ANSYS software package. The sizes and type of the finite element suitable for calculation on the basis of the solution in the program complex of the verification task were previously determined. The Kirsch problem was accepted as the verification problem.Result. The relative tangential stresses on the outer and inner lining contour, which allow reinforcement of the concrete lining at different depths of the tunnel, are determined. The tangential stresses in the adjacent rock massif are determined, allowing, if necessary, to assess the strength of the soil on the lining contour.Conclusion. The results of the study showed that the degree of anisotropy of the elastic properties of the soil massif significantly affects the stress state. When designing underground structures, it is neces-sary to take into account the anisotropy of the elastic properties of the soil mass; define in detail the physicomechanical properties of rocky soils and pay special attention to elastic characteristics. Ac-counting for transversal-isotropy leads to both an increase and a decrease in tangential stresses in the lining of the tunnel and in the rocky soil on the lining contour. In some respects, the elastic character-istics in orthogonal directions, in the lining and in the soil on the lining contour, there are no tensile stresses, which favorably affects the operation of the hydraulic tunnel.